Contribution about Social Responsibility for Business Organizations:Implementing the Micro-donation - Henryk J. Seeger (Journal of Management Practices, Humanities and Social Sciences, 2019)
This paper aimed to answer the question regarding the distribution of micro-donations. It focuses on investigating that how rounding-up the invoice amount of purchases could change the donation market. In order to do so an intensive literature review on ethics, Corporate Social Responsibility (CSR) and donations with a special focus on micro-donations was conducted. The findings from the literature review show that micro-donations can be used as a low threshold for customers to do good and as a starting point for bigger donations. Those findings were discussed in the light of how micro-donations can be perceived by customers and by corporations. Implementation strategies for micro-donations at different point-of-sales were analyzed within the work. The results of this literature review were compared with those of an empirical study that was also conducted in the course of the PhD. A quantitative survey taking place in both Germany and Romania including 16 closed-ended questions regarding people's attitude towards micro-donations was used to deepen the understanding of the topic. Analysis of the gathered data showed that, as was partially predicted by the findings from the literature review, the option to donate via micro-donations seem relevant especially for the young and the poor. Those usually very hard to reach demographics can with this measure be nudged into donating small amounts. In general, the paper was able to show that people do have a very positive attitude towards microdonations. Still, special education on the topic is needed in order to achieve optimal results.